Effect Of Npk Fertilizer On Growth And Production Of Sorghum (Sorghum bicolor (L.) Moench) Plants. - Millenia Feyby Klau; Stella M.T Tulung; Edy F. Lengkong (Jurnal Agroekoteknologi Terapan, 2023)
Sorghum (Sorghum bicolor (L.) Moench) is one type of cereal plant that has a high nutritional content. The increasing number of people in Indonesia every year is increasing this causes the need for food is also increasing. The current national food production has not been able to meet the needs of the community due to experts in the function of paddy fields, low soil fertility and lack of water, so it is necessary to look for food plants that are able to withstand dry land. Sorghum is one of the solutions for food crops that are able to grow on marginal land, wide adaptation, need little water, suitable for planting on dry land and when the weather is hot. This study aims to determine the effect of NPK fertilizer on the growth and production of sorghum. The study was carried out in Tombatu Village, Southeast Minahasa Regency which took place from August to November 2021. The study used a Randomized Block Design (RAK) consisting of five levels of treatment P1 100 kg/ha, P2 200 kg/ha, P3 300 kg/ha, P4 400 kg /ha, P5 500 kg/ha, the treatment was repeated 5 times. Observation variables included dry weight of plantings, planting seed weight, weight of 1000 seeds ,number of seeds filled with plantings, and number of empty seeds from planting . The results showed that a dose of 500 kg/ha of NPK fertilizer gave the best results for dry weight of the plant , planting seed weight, 1000 seed weight and number of seeds filled with plantings, while the number of empty were not affected by the dose of fertilizer given. Keywords: NPK fertilizer, Sorghum (Sorghum bicolor (L.) Moench) Abstrak Sorgum (Sorghum bicolor (L.) Moench) merupakan salah satu jenis tanaman serealia yang memiliki kandungan nutrisi yang tinggi. Peningkatan jumlah penduduk di Indonesia setiap tahun semakin meningkat hal ini menyebabkan kebutuhan pangan juga semakin meningkat. Produksi pangan nasional yang ada saat ini belum mampu memenuhi kebutuhan masyarakat akibat ahli fungsi lahan sawah, kesuburan tanah rendah dan kekurangan air, sehingga perlu dicari tanaman pangan yang mampu tahan pada lahan kering. Tanaman sorgum merupakan salah satu solusi tanaman pangan yang mampu tumbuh di lahan marginal, adaptasi luas, butuh sedikit air, cocok ditanam pada lahan kering dan saat cuaca panas. Penelitian ini bertujuan untuk mengetahui pengaruh pemberian pupuk NPK pada pertumbuhan dan produksi tanaman sorgum. Penelitian dilaksanakan di Desa Tombatu, Kabupaten Minahasa Tenggara yang berlangsung dari bulan Agustus sampai November 2021. Penelitian menggunakan Rancangan Acak Kelompok (RAK) yang terdiri atas lima taraf perlakuan P1 100 kg/ha, P2 200 kg/ha, P3 300 kg/ha, P4 400 kg/ha, P4 500 kg/ha, perlakuan tersebut diulang sebanyak 5 kali. Variabel pengamatan meliputi berat kering pertanaman, berat biji pertanaman, berat 1000 biji, jumlah biji berisi pertanaman, dan jumlah biji hampa pertanaman. Hasil penelitian menunjukkan bahwa pemberian dosis pupuk NPK 500 kg/ha memberi hasil terbaik untuk berat kering pertanaman, berat biji pertanaman, berat 1000 biji dan jumlah biji berisi pertanaman sedangkan jumlah biji hampa pertanaman tidak dipengaruhi oleh dosis pupuk yang diberikan. Kata Kunci: Pupuk NPK, Tanaman Sorgum (Sorghum bicolor (L.) Moench)